ANALISIS VARIASI GENETIK AMORPHOPHALLUS MUELLERI BLUME DARI BERBAGAI POPULASI DI JAWA TIMUR BERDASARKAN SEKUEN INTRON trnL - Erta Puri Rosidiani; Estri Laras Arumingtyas; Rodliyati Azrianingsih (Floribunda, 2013)
The objective of this study is to determine the genetic variability of porang atdifferent populations based on analysis of trnL intron sequences. Research was conducted in East Jawa, which is porang population at Jember (Mayang: MY), Malang (Lawang: LW, Kalipare: KP), Blitar (Brongkos: BL), Nganjuk (KPH tritik: TR), Madiun (Klangon: KL, KPH Saradan: MD), Bojonegoro (Klino: KN). Exploration conducted in 8 populations to take samples of young leaves as many as three sheets at two different individuals of each population. Then extract the DNA, and amplify the trnL intron using universal primers 'c' and 'd', then were purified and sequenced. The results of sequencing were analyzed the genetic variation and relationship based on Maximum Parsimony tree by MEGA5 software. Sequencing of 16 individuals porang, produce 13 individuals which have a clear chart chromatography which is resulting in the proper sequence and can be used in subsequent analyzes. The sequences showed the differences in nucleotide base composition of each individual. Six region is also known as conserved region, 52 sequences nucleotide variability, and 8 deletion. The phylogeny tree showed four clade Major. Porang were clustered randomly, not based on the population to which the individual is taken. Thus, the origin of porang at each study site cannot be identified based on the geographical analysis.